A Stastistical quality control analysis on Alcos Global Corporation - Herrin, Mark Andrew; Reyes, Jose Ricardo J.; Sabado, Jorge D.; Tiongson, Ciselle Myn C. (Diliman, Quezon City College of Engineering, 2001)
lcos Global Corporaton, formerly known as TOPY Industries Inc., is a 13 year-old corporation with plant at Bagumbayan, Quezon City. AGC manufactures plastic containers using injection molding and injection blow molding. Through thorough Problem Analysis, with the aid of problem identification tools such as Cause and Effect Diagrams, Pareto Chart and Histograms, the three problems, one attribute problem and two variable problems, on the manufacture of the 750 mL AVON Herbal Care bottles are identified. These are the Presence of Black Spots (attribute), the Excessive Product Volume, and the High Variance of Product Weight (variables). Before proceeding to further analysis, Test for Data Randomness, Goodness of Fit Test, Analysis of Variance (ANOVA), and Duncan's Multiple Range Test (DMRT), are utilized to verify the randomness of data, to determine the the distribution of data, to determine the significant factor(s), and to identify the specific factor that affects the variable, respectively. Statistical Process Control (SPC), through the use of appropriate control charts, is utilized for each problem. Process Capability Analysis is then performed on the problems on volume and weight. These analyses show that the process is out-of-control with respect to the manufacture of products with the correct volume, and is in-control with respect to the other two problems. Also, with the process capability indices below the value of one: 0.01 process capability index for product volume and 0.4959 process capability index for product weight, the process is inadequate and corrective action must begin immediately.
Consequently, recommendations are generated to address the problems. These are presented in flowcharts. Specifically, for the attribute problem, the recommendations, with the corresponding estimated cost in pesos, are: use "Keep Hopper Lid Close" sign (25.00) , record the number of surface rejects per hour (0.50 + 27.50/hr), construct the np control chart (27.50/hr), check if the process is in control (27.50/hr), post the control chart (27.50/hr + 3 per page), address the assignable causes, revise the control limits (27.50/hr), consult the Production Department (800/hr) and consult the supplier (1000/hr). For the variable problems, the recommendations with the corresponding estimated costs in pesos are: construct the control chart (27.50/hr), determine if the process is in-control (27.50/hr), post control chart (27.50/hr + 3 per page), address assignable causes (27.50/hr), revise control limits (27.50/hr), perform ANOVA (27.50/hr), perform DMRT (27.50/hr), perform Design of Experiments (DOE), and adjust machinable settings. (27.50/hr). Furthermore, determination of acceptance numbers standards for surface defects, and creation and use of a Control Chart and Standards Board are recommended for methods improvement. And a study on the use of chain sampling and a study on the use of switching rules for MIL STD 105E attributes inspection are recommended after performing the Acceptance Sampling Analysis.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Alcos Global Corporation; Manufacturing industry; Quality control